Validation of Boron Analytical Methods on Standard Reference Material Tomato Leaves from NIST No. 1573a with Isothermal Distillation by UV-Vis Spectrophotometry - Isna Lailatusholihah; Roto; Agus Kuncaka; Ninik Triayu Susparini (KOVALEN: Jurnal Riset Kimia, 2022)
Boron analysis by UV-Vis spectrophotometry has been developed through distilling triethoxy borane into the curcumin solution. In the distillation of ester borane, an esterification reaction occurs between borate and ethanol. Validation of isothermal distillation methods by UV-Vis spectrometry needs to be done to obtain specific, accurate, and reproducible results. The distillation for 24 hours at 25°C gave the optimum result. UV-Vis spectrophotometry wavelength was 535 nm. The standard curve was linear in the concentration range of 1-5 ppm (R2 = 0.9995) with a sensitivity of 0.0902 ppm-1, a limit of detection of 0.002±0.001 ppm, the limit of quantification of 0.006±0.001 ppm, and percent recovery of 88%.